1996
DOI: 10.1088/0967-1846/3/2/007
|View full text |Cite
|
Sign up to set email alerts
|

Distributed intelligent monitoring and reporting facilities

Abstract: Distributed intelligent monitoring and reporting facilities are of paramount importance in both service and network management as they provide the capability to monitor quality of service and utilisation parameters and notify degradation so that corrective action can be taken. By intelligent, we refer to the capability of performing the monitoring tasks in a way that has the smallest possible impact on the managed network, facilitates the observation and summarisation of information according to a number of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[3]: This is done by using intelligent agents to retrieve complex information about the status and the workload, thereby enabling service providers to ensure the continual uptime of a service object. Because of this, the service management often uses a distributed software architecture [10] where software agents are used to read the service data and correlate the information to provide a service operator with meaningful information.…”
Section: Service Management Fundamentalsmentioning
confidence: 99%
“…[3]: This is done by using intelligent agents to retrieve complex information about the status and the workload, thereby enabling service providers to ensure the continual uptime of a service object. Because of this, the service management often uses a distributed software architecture [10] where software agents are used to read the service data and correlate the information to provide a service operator with meaningful information.…”
Section: Service Management Fundamentalsmentioning
confidence: 99%
“…for providing more sophisticated features that were not thought out in advance, needs to go through the full research, standardization and deployment cycle. For example, [14] identified additional functionality that combines the capabilities of metric monitoring and summarization objects in a powerful fashion but such additions need to go through a new standardization cycle. The specification of the OSI-SM systems management functions took a long time and is partly responsible for the perceived complexity and lateness in the deployment of OSI-SM-based network elements.…”
Section: Static Performance Monitoringmentioning
confidence: 99%
“…This concept has its parallel in traditional management systems through the use of the OSI management Systems Management Functions (SMFs) [25] for event forwarding and logging, resource monitoring [26] [27], and testing [28], albeit in a more limited way. Previous research work [29] [30] has demonstrated how clients can take advantage of these generic facilities to simplify the construction of intelligent clients.…”
Section: Fig 4 Connectivity Providers Hierarchymentioning
confidence: 99%